Association of Obesity with Hypertension in Adult Female - Yeasmin, Nahid; Mahmuda, Sayeeda; Akther, Shamima; Begum, Khadija; Salehin, Masud; Yeasmin, Sultana (Bangladesh Journal of Medicine, 2017)
Background: Incidence of hypertension in female is increasing throughout the world, leading to life threatening medical problem like cardiovascular diseases, stroke. An association between hypertension and obesity has been identified. Objectives : The study was carried out to observe the association of obesity with hypertension in adult female. Methods : This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of one hundred female subjects were selected with age ranging from30 to50 years. Among them 50 hypertensive female subjects were included from out-patient department of Medicine, Dhaka medical college Hospital, Dhaka as study group(B) and 50 apparently healthy female were taken as control group(A) for comparison Waist circumference(WC) was measured and body mass index (BMI) was calculated in both groups. Data was analyzed by Unpaired Students t test and Pearsons correlation co-efficient (r) test as applicable. Results: The value of waist circumference was higher in hypertensive subjects than those of nonhypertensive female and result was statistically significant. Body mass index value was significantly (p<0.001) higher in hypertensive subjects in comparison to those of non-hypertensive subjects. In hypertensive subjects waist circumference and body mass index values were higher and showed significant positive correlation with systolic and diastolic blood pressure. Conclusion: Present study revealed that hypertension has positive and significant relationship with waist circumference and body mass index. Bangladesh J Medicine Jan 2017; 28(1) : 28-33